The new rules of marketing & PR : how to use content marketing, podcasting, social media, AI, live video, and newsjacking to reach buyers directly - Scott, David Meerman (John Wiley & Sons, Inc., 2022)
"The eighth edition of the pioneering guide to generating attention for your idea or business, packed with new and updated information In the Digital Age, marketing tactics seem to change on a day-to-day basis. As the ways we communicate continue to evolve, keeping pace with the latest trends in social media, the newest online videos, the latest mobile apps, and all the other high-tech influences can seem an almost impossible task. How can you keep your product or service from getting lost in the digital clutter? The eighth edition of The New Rules of Marketing & PRA provides everything you need to speak directly to your audience, make a strong personal connection, and generate the best kind of attention for your business. An international bestseller with more than 400,000 copies sold in twenty-nine languages, this revolutionary guide gives you a proven, step-by-step plan for leveraging the power of technology to get your message seen and heard by the right people at the right time. You will learn the latest approaches for highly effective public relations, marketing, and customer communicationsâ€all at a fraction of the cost of traditional advertising! The latest edition ofA The New Rules of Marketing & PRA has been completely revised and updated to present more innovative methods and cutting-edge strategies than ever. The new content shows you how to harness AI and machine learning to automate routine tasks so you can focus on marketing and PR strategy. Most notably, the eighth edition addresses how the pandemic has changed marketing and PR, including examples and stories about virtual events and remote marketing strategies. Still the definitive guide on the future of marketing, this must-have resource will help you: Incorporate the new rules that will keep you ahead of the digital marketing curve. Make your marketing and public relations real-time by incorporating techniques like newsjacking to generate instant attention when your audience is eager to hear from you. Use web-based communication technologies to their fullest potential. Gain valuable insights through compelling case studies and real-world examples. Take advantage of marketing opportunities on platforms like TikTok and Clubhouse The eighth edition ofÂ The New Rules of Marketing and PR: How to Use Content Marketing, Podcasting, Social Media, AI, Live Video, and Newsjacking to Reach Buyers DirectlyÂ is the ideal resource for entrepreneurs, business owners, marketers, PR professionals, and managers in organizations of all types and sizes"--